The functional approach in aspect of the innovations fundamental in medicine - Olga Alekseevna Butova (Наука. Инновации. Технологии)
The functional approach to the analysis of linkages morph functional in characteristics and parameters of the element status of the female organism in carriage disorder exposed optimal adaptive capability during the second childhood period and adolescence, and disadaptive changes in life-support systems in the adolescent period of ontogeny. Diagnostic algorithm which had been used in combination with the research of the cell proteome will allow to approach to innovative methods of diagnosis and carriage disorder.